Islamic banking product acceptance among students and working employees in Malaysia - Hassan, Rusni; Yusof, Yuartika (Medwell Journals, 2016)
Islamic banking is the fast growing industry serve financing products vis-a-vis conventional banking to the customers. Customer is an important agent in a product sale. They determine the product acceptance in a market. University students and working employee who are also act as customers need Islamic banking products in their daily life. Customers having insufficient product knowledge, religious practice and lower perception on competitive pricing of certain Islamic banking products lead to poor Islamic banking product acceptance. The objectives of this study were assessing the Islamic banking product knowledge, religious practice and perception on competitive pricing among students and working employees who lived in Klang valley. The 300 respondents (144 males and 156 females) were participated in this study. The instrument used was a four-section questionnaire from previous studies and some were modified to suit the need of the study. The questionnaire consist twenty five questions overall and every section consists one factor to determine the product acceptance. SPSS Version 20.0 is adopted to measure the findings of the study. The results of this study confirmed that customer's product knowledge and religious practice are high thus resulted to Islamic banking product acceptance. On the other hand, customers have lower perception on competitive pricing rejects the product acceptance. The researchers recommend on strengthening the knowledge, religiosity and competitive pricing through Islamic banks as a medium.